The Need To Use Interdiscipline Approaches in the Activities of A Military Researcher - Khudoykulov Yulchi Azamkulovich (Scientific Trends, 2025)
This article analyzes the need to use interdisciplinary approaches to the formation of new knowledge in the activities of researchers conducting military research. Modern research in the military field requires the integration of disciplines, including the development of interdisciplinary and transdisciplinary paradigms.
Keywords: military field, military researcher, interdisciplinary approach, interdisciplinary integration, paradigm, military strategy, artificial intelligence, cybersecurity.